Can willingness-to-pay values be manipulated? Evidence from an experiment on organic food in China - Xiaohua Yu; Binjian Yan; Zhifeng Gao (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Human behaviours are driven by two different types of motives: implicit and explicit motives. Psychologists have developed two main tools, namely time pressure and cognitive load, to disentangle the two motives. It implies that the values of willingness to pay (WTP) are sensitive to time pressure and cognitive load levels in practice. An experiment with 233 students is conducted in China to study the willingness to pay for organic food with consideration of different time pressures and cognitive load levels. Results show that increasing cognitive load could significantly reduce consumers' WTP for organic food; and time pressure does not have significant impact on WTP values. Such results remind us of being particularly cautious about the cognitive load situations of respondents during a WTP survey. Otherwise, the WTP results are unstable and inconvincible.
Keywords: C91; Q13; 330; Motives; Time Pressure; Cognitive Load; WTP; Organic Food; Experiments